Catalytic Strategies toward Selective Hydrogenation of Aromatic Ketones and Phenols: Facile Synthesis of Cyclohexyl Ketones - Wei, Yu; Zeng, Xiaoming (Synlett, 2016)
Selective hydrogenation of aromatic ketones and phenols by the reduction of aromatic groups, with the retention of an easily reducible carbonyl functionality in the final products, provides a practically useful route to fundamentally interesting cyclohexyl ketones and cyclohexanones, but the achievement thereof remains a great challenge. Recently, however, much progress in this area has been made with the use of rhodium and palladium catalysis. We now highlight the achievements made in the selective hydrogenation of aromatic ketones and phenols by reduction of the aromatic motifs.1 Introduction2 Chemoselective Hydrogenation of Aromatic Ketones by Reducing the Aromatic Scaffolds3 Selective Hydrogenation of Phenols to Cyclohexanones4 Conclusion
Keywords: hydrogenation; chemoselectivity; aromatic ketones; phenols; catalysis